Gender Equality on The Label’s Children’s Book Covers Boitatá Editorial: A Multimodal Look (Global Journal of Human-Social Science, 2024)
In recent decades the publishing market and the classroom have sought to accept the demands defended by social movements regarding the promotion of affirmative actions in favor of equality and diversity In this context issues of gender race as well as female representation in different spaces stand out In this sense this research aims to analyze the representation of gender equality on the covers of four children s books published by Boitat the children s seal of Boitempo Editora based on the foundations of Multimodal Social Semiotics KRESS VAN LEEUWEN 1996 which conceives language as a semiotic system of choices and is not restricted only to the linguistic semiotic mode but to other semiotic modes such as the visual As for the methodological categories of analysis the visual metafunctions proposed by the Grammar of Visual Design were adopted precisely the representational interactive and compositional meanings The main results of the study point to the transgression of sexist imagery standards for the representation of girls and women as well as the need for teachers to look at works that represent gender equality and diversity in a more inclusive and plural way
Keywords: multimodal social semiotics; grammar of visual design; gender equality; children's book covers; boitatá publishing seal